Lead perovskites as CEνNS detectors - Jesús-Valls, César; Sánchez, Federico (Frontiers in Physics, 2023)
Introduction: The recent discovery of coherent elastic neutrino-nucleus scattering (CEvNS) has created new opportunities to detect and study neutrinos. The interaction cross section in CEvNS scales quadratically with the number of neutrons, making heavy-nuclei targets such as active lead-based detectors ideal. Lead perovskites have emerged in the last decade as revolutionary materials for radiation detection due to their heavy and flexible element composition and their unique optoelectronic properties that result in an excellent energy resolution at an economic cost. Methodology: In this study, we discuss, for the first time, the physics potential and feasibility of building neutrino detectors using semiconductor lead perovskite crystals as a target. Results and Discussion: We indicate that existing data with x-rays suggest the suitability of existing lead perovskite sensors to study CEvNS using neutrinos from π decay at rest (π- DAR) sources. Although dedicated research and development will be necessary, we have found significant benefits and no inherent obstacles for the development of lead perovskites as CEvNS detectors.